PENGENDALIAN EMISI GAS BUANG BOILER BATUBARA DENGAN SISTEM ABSORBSI - Silvy Djayanti; P Purwanto; Setia Budi Sasongko (School of Postgraduate Studies, Diponegoro Univer, 2011)
Absorption study of emission gas (SO2, NO2, CO, and CO2) from coal boiler with NaOH absorber waste of textile industry has been done. Acid gasses neutralized and particulate trapped by NaOH solution. NaOH was chosen for efficiency of waste neutralized and obtained from waste absorber and conventional textile finishing process (NaOH) with the concentration of 100 mol/m3. Emitted disposal gas concentration at flow rate 500, 1000, 2500, 5000, and 10,000 L/hour before and after absorption was measured and analyzed using MATLAB and EXCEL software. There was no significant difference between observation and theoretical calculation data (P<0,05). At flow rate 2500 L/hour concentration of emission gas have shown under threshold values. A liquid-gas absorption model that obtained form this study could be used to predict optimum flow rate required for reducing the emission gas concentration to the quality threshold values.